Imaging in myopia: potential biomarkers, current challenges and future developments. Issue 6 (12th January 2019) - Ang, Marcus; Wong, Chee Wai; Hoang, Quan V; Cheung, Gemmy Chui Ming; Lee, Shu Yen; Chia, Audrey; Saw, Seang Mei; Ohno-Matsui, Kyoko; Schmetterer, Leopold
Abstract : Myopia is rapidly increasing in Asia and around the world, while it is recognised that complications from high myopia may cause significant visual impairment. Thus, imaging the myopic eye is important for the diagnosis of sight-threatening complications, monitoring of disease progression and evaluation of treatments. For example, recent advances in high-resolution imaging using optical coherence tomography may delineate early myopic macula pathology, optical coherence tomography angiography may aid early choroidal neovascularisation detection, while multimodal imaging is important for monitoring treatment response. However, imaging the eye with high myopia accurately has its challenges and limitations, which are important for clinicians to understand in order to choose the best imaging modality and interpret the images accurately. In this review, we present the current imaging modalities available from the anterior to posterior segment of the myopic eye, including the optic nerve. We summarise the clinical indications, image interpretation and future developments that may overcome current technological limitations. We also discuss potential biomarkers for myopic progression or development of complications, including basement membrane defects, and choroidal atrophy or choroidal thickness measurements. Finally, we present future developments in the field of myopia imaging, such as photoacoustic imaging and corneal or scleral biomechanics, which may lead to innovative treatment modalities for myopia.